Transcription Factor Retinoid-Related Orphan Receptor γt: A Promising Target for the Treatment of Psoriasis - Tang, Lipeng; Yang, Xiaozhi; Liang, Yongxin; Xie, Hesong; Dai, Zhenhua; Zheng, Guangjuan (Frontiers in Immunology, 2018)
Psoriasis, which is a common chronic inflammatory skin disease, endangers human health and brings about a major economic burden worldwide. To date, treatments for psoriasis remain unsatisfied because of their clinical limitations and various side effects. Thus, developing a safer and more effective therapy for psoriasis is compelling. Previous studies have explicitly shown that psoriasis is an autoimmune disease that is predominantly mediated by T helper 17 (Th17) cells, which express high levels of Interleukin-17 (IL-17) in response to Interleukin-23 (IL-23). The discovery of the IL-23-Th17-IL-17 axis in the development of psoriasis has led to the paradigm shift of understanding pathogenesis of psoriasis. Although anti-IL-17 antibodies show marked clinical efficacy in treating psoriasis, compared with antibodies targeting IL-17A or IL-17R alone, targeting Th17 cells themselves may have a maximal benefit by affecting multiple proinflammatory cytokines, including IL-17A, IL-17F, IL-22 and GMCSF, which likely act synergistically to drive skin inflammation in psoriasis. In this review, we mainly focus on the critical role of Th17 cells in the pathogenesis of psoriasis. Especially, we explore the small molecules that target RORγt (retinoid-related orphan receptor γt), a vital transcription factor for Th17 cells. Given that RORγt is the lineage-defining transcription factor for Th17 cell differentiation, targeting RORγt via small molecular inverse agonists may be a promising strategy for the treatment of Th17-mediated psoriasis.